Altered epigenetic features in circulating nucleosomes in idiopathic pulmonary fibrosis - Guiot, J. (Clin Epigenetics, 2017)
BACKGROUND: Idiopathic pulmonary fibrosis (IPF) is a progressive, fatal lung disorder of unknown origin with a highly variable and unpredictable clinical course. Polymorphisms and environmentally induced epigenetic variations seem to determine individual susceptibility to the development of lung fibrosis. METHODS: We have studied circulating epitopes on cell-free nucleosomes (cfnucleosomes) in 50 IPF patients. We have compared untreated IPF (n = 23) with IPF receiving antifibrotic therapy (n = 27) and healthy subjects (HS) (n = 27). We analyzed serum levels of five cfnucleosomes including bound HMGB1 (nucleosomes adducted to high-mobility growth protein B1), mH2A1.1 (nucleosomes containing the histone variant mH2A1.1), 5mC (nucleosomes associated with methylated DNA), and H3K9Ac and H3K27Ac (nucleosomes associated with histone H3 acetylated at lysine 9 or 27 residue). RESULTS: Our findings showed that serum levels of bound HMGB1, mH2A1.1, 5mC, H3K9Ac, and H3K27Ac were significantly lower in IPF patients than in HS (p < 0.001, p < 0.001, p < 0.01, p < 0.001, and p < 0.0001, respectively). Moreover, we found differences in epigenetic profiles between untreated IPF patients and those receiving anti-fibrotic therapy with mH2A1.1 and 5mC being significantly lower in untreated than in treated patients (p < 0.01 and p < 0.05, respectively). Combination of four cfnucleosomes (HMGB1, 5mC, H3K9Ac, and H3K27Ac) allow to discriminate IPF vs HS with a good coefficient of determination (R (2) = 0.681). The AUC for the ROC curve computed by this logistic regression was 0.93 (p < 0.001) with 91% sensitivity at 80% specificity. CONCLUSION: Our observations showed that cfnucleosomes (bound HMGB1, mH2A1.1, 5mC, H3K9Ac, and H3K27Ac) might have potential as biomarkers for diagnosis and treatment response. These results deserve further validation in longitudinal cohorts.